Survey of Integrated Pest Management (IPM) Practice in Vegetable Crops of Rupandehi District, Western Nepal - Thapa, Chandra Bahadur (International Journal of Applied Sciences and Biotechnology, 2017)
In the present study, documentation of farmer’s knowledge on Integrated Pest Management (IPM) was carried out in Rupandehi district during the year 2016. The objective of this paper is to assess the knowledge of farmers about IPM and its effectiveness in this district. It was carried out by conducting semi-structured interview with the participants of IPM FFS, vegetable growing farmers, stakeholders and local people with the help of standard questionnaire, Focus Group Discussion (FGD) and key informant interview. The IPM program is found to be conducted by an international non-government organization viz. Food and Agriculture Organization (FAO) and government organizations viz. Plant Protection Directorate (PPD), Agronomy Development Directorate (ADD) and District Agriculture Development Organization (DADO) through Farmer’s Field School (FFS) in this district. In total forty IPM FFS was conducted from 1998 to 2015 which provided training about IPM in rice and vegetable crops to 1057 farmers in which 393 were male and 664 female. Although a significant difference has been found in the knowledge about the amount of pesticide used, biological method of pest control for IPM by FFS participant and nonparticipant farmers, it is not observed in their behavior during the cultivation of crops in the farm. The result showed that only 5% of participants of Farmer’s Field School (FFS) are following IPM practices in their own farm after taking training. Int. J. Appl. Sci. Biotechnol. Vol 5(2): 237-242